ASPEK HUKUM DALAM PENGABAIAN PEMBAYARAN UTANG OLEH DIREKSI YANG MENGAKIBATKAN KEPAILITAN PERSEROAN: Legal Aspects of Directors’ Negligence in Debt Payment Leading to Corporate Bankruptcy - Ibrahim Aulia Akbar; Arif Wicaksana (Reformasi Hukum Trisakti, 2026)
The application of the duty of care principle constitutes a primary obligation of directors in carrying out corporate management functions, particularly in the management of debt repayment obligations to creditors. In Indonesian bankruptcy law practice, corporate bankruptcy is not always caused by a condition of inability to pay (insolvency), but may occur as a result of directors’ negligence in exercising the principle of prudence, even though the company factually still possesses adequate financial capacity and sufficient assets. The legal issue examined in this study concerns the legal aspects of directors’ neglect of debt repayment that results in corporate bankruptcy. This research employs a normative legal research method using a statutory approach. The Decision of the Commercial Court at the Semarang District Court Number 2/Pdt.Sus-Pailit/2024/PN Niaga Smg is used as a factual reference to illustrate the phenomenon of corporate bankruptcy involving a relatively small amount of debt compared to the assets owned by the company. The findings and conclusion indicate that directors’ negligence in managing debt repayment obligations may be classified as a violation of the duty of care principle, which opens the possibility of corporate bankruptcy, regardless of the company’s financial condition that remains substantively sound.